The symbolism of the street in portuguese contention - Accornero, G.; Carvalho, T.; Pinto, P. R. (Symbolic objects in contentious politics, 2023)
The street has long been a disputed symbol in Portuguese contentious history. Usually understood as endowing political legitimacy, sometimes as an inherently emancipatory space, and latterly as an unsafe, risky, and unsheltered space, the street has long featured at the center of Portuguese democracy and political discourse.2 But the street is not just a space used or occupied by contentious players, or only a symbol mobilized in their discourses. In the Portuguese cultural context, the materiality and physicality of street occupations offer a distinct potential for contentions to invoke notions of legitimacy and emancipation. In relational terms, the street is mobilized by social movements, trade unions, and political parties to narrate their struggles in a democratic space. The importance of the street extends to Portuguese pop culture, as seen in the lyrics quoted above. In the mid-1980s, Xutos e Pontapés, one of the most emblematic bands in the Portuguese rock scene, made it the main topic of one their songs. Their 1987 release, “Go Out to the Street,” captures the spirit of what we focus on in this chapter: the importance of the street as the site of political action in Portuguese contention.